2012
DOI: 10.1128/jvi.06202-11
|View full text |Cite
|
Sign up to set email alerts
|

Activation of NF-κB in CD8 + Dendritic Cells Ex Vivo by the γ 1 34.5 Null Mutant Correlates with Immunity against Herpes Simplex Virus 1

Abstract: The ␥ 1 34.5 protein of herpes simplex viruses (HSV) is essential for virulence. Accordingly, an HSV mutant lacking ␥ 1 34.5 is attenuated in vivo. Despite its vaccine potential, the mechanism by which the ␥ 1 34.5 null mutant triggers protective immunity is unknown. In this report we show that vaccination with the ␥ 1 34.5 null mutant protects against lethal challenge from wild-type virus via IB kinase in dendritic cells (DCs), which sense virus-associated molecular patterns. Unlike mock-treated DCs, DCs prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 70 publications
(105 reference statements)
0
12
0
Order By: Relevance
“…ϩ DCs (56). The large genome of HSV-1 therefore enables the encoding of numerous proteins that modulate host innate immune responses.…”
mentioning
confidence: 99%
“…ϩ DCs (56). The large genome of HSV-1 therefore enables the encoding of numerous proteins that modulate host innate immune responses.…”
mentioning
confidence: 99%
“…ICP27, an immediate early gene product of HSV-1, has been shown to antagonize NF-B signaling (17). The ␥ 1 34.5 protein, an HSV-1-encoded late-gene product, inhibits activation of NF-B in CD8 ϩ dendritic cells (DCs) (18). Vhs, a tegument protein, blocks the early replication-independent activation of NF-B in HSV-1-infected DCs (19).…”
mentioning
confidence: 99%
“…Alternatively, the model HEK-293T cells have been employed in such studies (10). The roles of the various branches of the innate response to HSV in cell targets of the infection, e.g., epithelial and neuronal cells, have so far received little attention, apart from a number of studies focused on in vivo or ex vivo responses (9,(15)(16)(17).Recently, we reported that ␣v␤3 integrin serves as a novel sensing system for HSV (18). It elicits the production of IFN-␣ and -␤ and a specific set of cytokines and receptors, interleukin-10 (IL-10), IL-2, and IL2R, as well as NF-B activation (18).…”
mentioning
confidence: 99%
“…Alternatively, the model HEK-293T cells have been employed in such studies (10). The roles of the various branches of the innate response to HSV in cell targets of the infection, e.g., epithelial and neuronal cells, have so far received little attention, apart from a number of studies focused on in vivo or ex vivo responses (9,(15)(16)(17).…”
mentioning
confidence: 99%
See 1 more Smart Citation